Assurance of Learning (AoL) and AACSB's 2020 Business Accreditation Standards: A conversation with Marine Condette - Isabelle J. Fagnot (Organization Management Journal (OMJ), 2023)
Purpose - This paper aims to discuss Assurance of Learning (AoL) and 2020 Standards from Association to Advance Collegiate Schools of Business (AACSB) International with Marine Condette from AACSB. Design/methodology/approach - Structured interview. Findings - Changes following the 2020 Standards. Originality/value - This paper is an interview with Marine Condette from the AACSB Europe, Middle East and Africa (EMEA) office on AoL discussing as well the changes with the 2020 AACSB Standards.
Keywords: 650; AACSB; Assurance of Learning; Continuous improvement; Higher education; International accreditation